Characteristics of patients with dyslipidemia treated in routine care setting in China. (1st January 2019) - Liu, Gordon; Shepherd, Jason; Rane, Pratik; Zhao, Zhongyun; Bailey, Hollie; Williams, Nathan; Qian, Yi
Abstract: Objective: To describe characteristics of patients with dyslipidemia treated in routine care in China overall and stratified by diabetes and atherosclerotic cardiovascular disease (ASCVD). Methods: This study used data from a cross-sectional survey conducted in China in 2017 under the Dyslipidemia Disease Specific Programme (DSP). Each surveyed physician provided information including demographics, dyslipidemia diagnosis and treatment history, lab values on at least 8 patients currently treated for dyslipidemia with oversampling of patients with ASCVD or diabetes mellitus diagnosis at the time of survey. A related patient survey assessed treatment adherence and satisfaction. Results: This study included 195 physicians (40 endocrinologists, 75 internists, 80 cardiologists) who provided data on 1870 patients (852 with diabetes; 1018 patients without diabetes). Among patients with diabetes, 279 had ASCVD and 573 did not (non-ASCVD). In the diabetic population, patients with ASCVD were older (67.3 vs. 62.1 years), more often had caregiver support (34 vs. 14%), and had higher average LDL-C at diagnosis (172.4 vs. 167.4 mg/dL) compared to their non-ASCVD counterparts. Findings were similar for non-diabetic patients (ASCVD: 323 patients; non-ASCVD: 695) patients. In all four subgroups, 46–54% of patients reported low treatment adherence, and fewer than half expressed satisfaction with their cholesterol control, and 2–5% had LDL-C < 70 mg/dL at their most recent assessment. Conclusions: Among patients with dyslipidemia, those with ASCVD had higher LDL-C levels than patients without ASCVD, and many required caregiving. Low levels of treatment adherence, LDL-C control, and patient satisfaction suggest opportunities to improve care for Chinese patients with dyslipidemia.